Identification of Types of Pests and Diseases of Cauliflower Plants (Brassica oleracea var. botrytis L) in Gonaman Village, Koripan, Matesih District, Karanganyar - Hanik, Nur Rokhimah; Armania, Vallery; Ardiansyah, Muhammad Ilham; Marta, Fadhilah; Hidayad, Muhammad Nur; Saputra, Dian Andhi; Mardyah, Muthia; Pangestu, Prestiani Yulia; Yoshia, Selumiel; Sarima, Sarima (Jurnal Biologi Tropis, 2025)
Cauliflower (Brassica oleracea var. botrytis L.) during its development period needs to be controlled by pests and diseases, because at that time the flowers or krobs come out and will determine the quality and quantity of its production. This research is conducted to characterize and differentiate various types of pests and diseases found in cauliflower plants in the gardens of Gonaman Village, Koripan, Matesih District, Karanganyar. This research employs a methodology based on descriptive qualitative analysis. The tools utilized in this study include a mobile phone, writing instruments, and observation sheets. The research subjects consist of various pests and diseases identified in the garden area. Data collection by observation of the garden and direct interviews with garden owners. For data analysis and validation, qualitative descriptive techniques are used with additional interview activities with cauliflower farmers and literature studies. Based on the results of the study, eight pests have been found, namely; Whitefly / Cabuk (Aphis brassicae), Thrips (Thrips tabasi), Whitefly (Aleyrodidae sp), Crop Caterpillar (Crocidolomia binotalis), Ladybug (Illeis galbula), Brown grasshopper (Valanga nigricornis), Leaf beetle (Aluacphora sp), Leaf caterpillar (Plutella xylostella). And four diseases were found; Alternaria brassicae fungus, bacterial rot by Pectobacterium carotovorum, Erwinnia carotovora bacteria, and Xanthomonas camprestis bacteria. The visible symptoms are damage to the leaves, yellow, brownish to blackish leaves, rotten and wilted flowers so that they can reduce the harvest. Pest and disease control can be done by spraying pesticides, fungicides once a week, maintaining land cleanliness, maintaining planting distance, selecting healthy seeds, and providing lime and boren. For further research, it should be done for several days, in the morning and evening when insects are active.